Network-based modelling reveals cell-type enriched patterns of non-coding RNA regulation during human skeletal muscle remodelling - Mcleod, Jonathan C; Lim, Changhyun; Stokes, Tanner; Sharif, Jalil-Ahmad; Zeynalli, Vagif; Wiens, Lucas; D’Souza, Alysha C; Colenso-Semple, Lauren; McKendry, James; Morton, Robert W; Mitchell, Cameron J; Oikawa, Sara Y; et al. (NAR molecular medicine, 2024)
A majority of human genes produce non-protein-coding RNA (ncRNA), and some have roles in development and disease. Neither ncRNA nor human skeletal muscle is ideally studied using short-read sequencing, so we used a customized RNA pipeline and network modelling to study cell-type specific ncRNA responses during muscle growth at scale. We completed five human resistance-training studies (n = 144 subjects), identifying 61% who successfully accrued muscle-mass. We produced 288 transcriptome-wide profiles and found 110 ncRNAs linked to muscle growth in vivo, while a transcriptome-driven network model demonstrated interactions via a number of discrete functional pathways and single-cell types. This analysis included established hypertrophy-related ncRNAs, including CYTOR—which was leukocyte-associated (false discovery rate [FDR] = 4.9 × 10−7). Novel hypertrophy-linked ncRNAs included PPP1CB-DT (myofibril assembly genes, FDR = 8.15 × 10−8), and EEF1A1P24 and TMSB4XP8 (vascular remodelling and angiogenesis genes, FDR = 2.77 × 10−5). We also discovered that hypertrophy lncRNA MYREM shows a specific myonuclear expression pattern in vivo. Our multi-layered analyses established that single-cell-associated ncRNA are identifiable from bulk muscle transcriptomic data and that hypertrophy-linked ncRNA genes mediate their association with muscle growth via multiple cell types and a set of interacting pathways.